Adaptive Tropical Waterschappen Model for Sustainable Wetland Governance in Indonesia - Setiawan, Denny; Claudia, Mieske; Yunani, Ahmad (Jurnal Manajemen, 2026)
Wetlands in Indonesia play a strategic role in food security, water regulation, carbon storage, and local livelihoods, yet their governance remains constrained by fragmented institutions, weak infrastructure maintenance, limited participation, and ecological degradation. This article aims to develop an adaptive governance model for sustainable wetland governance in Indonesia by translating selected principles of the Dutch Waterschappen system into tropical wetland settings. The study applies a qualitative descriptive-comparative conceptual design based on literature review, policy review, and illustrative analysis of five Indonesian wetland contexts. The findings identify four recurring governance problems: hydrological–administrative misalignment, weak institutional continuity, limited participatory integration, and low implementation capacity. In response, the article proposes the Tropical Waterschappen model, consisting of six pillars: hydrology-based institutional alignment, inclusive multi-stakeholder governance, collaborative and sustainable financing, adaptive spatial and ecological management, transparent information and participatory monitoring, and implementation capacity through human capital and institutional behavior. The model contributes to wetland governance literature by linking institutional design with an implementation mechanism grounded in human capital and behavioral readiness. Practically, it offers a management-oriented framework for strengthening coordination, participation, financing continuity, and adaptive ecological governance in Indonesian wetlands.